Efforts to increase enthusiasm for learning through a simple lava lamp-based experiment learning - Sally Geba Latami Telaumbanua (Universitas Pendidikan Indonesia, 2025)
Education is one of the most essential requirements for national development, as quality education produces quality human beings. The purpose of this study is to create a pleasant learning environment that facilitates students' understanding of the material and encourages active class participation, while also examining the relationship to the Sustainable Development Goals (SDGs). Through research and development (RnD) method in the Thematic KKN service method of the Universitas Pendidikan Indonesia 2022/2023 with the theme